Environmental Reporting Practices of Top Public Listed Companies: Analyzing Pre-Post Corporate Social Responsibility Framework - Haslinda Yusoff; Siti Hazwani Kamaruddin; Erlane K. Ghani (Indonesian Journal of Sustainability Accounting and Management, 2018)
This study examines the environmental reporting practices of the top public listed companies in Malaysia, before and after the introduction of the Corporate Social Responsibility Framework. Specifically, this study examines the level of extensiveness of environmental disclosures among the top public listed companies. In addition, this study identifies the factors that influence the environmental reporting practices of the top public listed companies. The factors examined in this study include industry sector, ISO certification, size and profitability. Using content analysis on the corporate annual reports of 50 top publicly listed companies, this study shows that greater environmental reporting practices was found in the post-period of the framework. This study also shows that the factors influencing environmental reporting practices among the top public listed companies vary between the pre-period and the post-period. The findings of this study implicate that regulatory initiatives represent an influential factor in promoting environmental accountability via reporting practices among the companies in Malaysia.